Design and synthesis of novel quinazolin‐4(1H)‐one derivatives as potent and selective inhibitors targeting AKR1B1. Issue 4 (27th January 2023) - Han, Zhongfei; Li, Jiahui; Xu, Zilu; Su, Yu; Wang, Yihan; Zhuo, Lili; Du, Jiaming; Zhu, Changjin; Hao, Xin
Abstract: Inhibition of aldose reductase (AKR1B1) is a promising option for the treatment of diabetic complications. However, most of the developed small molecule inhibitors lack selectivity or suffer from low bioactivity. To address this limitation, a novel series of quinazolin‐4(1 H )‐one derivatives as potent and selective inhibitors of AKR1B1 were designed and synthesized. Aldose reductase inhibitory activities of the novel compounds were characterized by IC50 values ranging from 0.015 to 31.497 μM. Markedly enhanced selectivity of these derivatives was also recorded, which was further supported by docking studies. Of these inhibitors, compound 5g exhibited the highest inhibition activity with selectivity indices reaching 1190.8. The structure–activity relationship highlighted the importance of N1‐acetic acid and N3‐benzyl groups with electron‐withdrawing substituents on the quinazolin‐4(1 H )‐one scaffold for the construction of efficient and selective AKR1B1 inhibitors. Abstract : A novel series of quinazolin‐4(1 H )‐one derivatives were designed and synthesized as potent and selective inhibitors of aldose reductase (AKR1B1). Structure–activity relationship studies point to the importance of N1‐acetic acid and N3‐benzyl groups with electron‐withdrawing substituents on the quinazolin‐4(1 H )‐one scaffold for the construction of efficient and selective AKR1B1 inhibitors.